2015
DOI: 10.1175/jpo-d-14-0163.1
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Variability of the Atlantic Meridional Overturning Circulation at Interannual-to-Multidecadal Time Scales

Abstract: The low-frequency variability of the Atlantic meridional overturning circulation (AMOC) is investigated from 2, 1 /48, and 1 /128 global ocean-sea ice simulations, with a specific focus on its internally generated (i.e., ''intrinsic'') component. A 327-yr climatological 1 /48 simulation, driven by a repeated seasonal cycle (i.e., a forcing devoid of interannual time scales), is shown to spontaneously generate a significant fraction R of the interannual-to-decadal AMOC variance obtained in a 50-yr ''fully force… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
81
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(103 citation statements)
references
References 42 publications
(55 reference statements)
21
81
1
Order By: Relevance
“…They found a strong response with a resonancelike behavior for periods longer than 15 yr. Delworth and Greatbatch (2000) used a low-resolution but otherwise realistic global model to show that the dominant variability of the MOC was externally forced by changes in air-sea heat fluxes. Grégorio et al (2015) came to a similar conclusion, particularly at high latitudes, with an eddy-resolving Atlantic sector general circulation model forced by realistic atmospheric fluxes.…”
Section: Introductionsupporting
confidence: 58%
“…They found a strong response with a resonancelike behavior for periods longer than 15 yr. Delworth and Greatbatch (2000) used a low-resolution but otherwise realistic global model to show that the dominant variability of the MOC was externally forced by changes in air-sea heat fluxes. Grégorio et al (2015) came to a similar conclusion, particularly at high latitudes, with an eddy-resolving Atlantic sector general circulation model forced by realistic atmospheric fluxes.…”
Section: Introductionsupporting
confidence: 58%
“…These temperature anomalies were computed by first removing the long-term non-linear trend of the time series derived from a local regression model (as in Grégorio et al, 2015). This detrending step acts as a non-linear high-pass temporal filter with negligible end-point effect also called local regression (LOESS) detrending (e.g.…”
Section: Probabilistic Interpretationmentioning
confidence: 99%
“…6, along with their simulated counterpart from E-ORCA025. They were computed in geopotential coordinates as in Zhang (2010) and Grégorio et al (2015), and are shown after LOESS detrending and after removing the mean seasonal cycle.…”
Section: Toward Probabilistic Climate Diagnosticsmentioning
confidence: 99%
See 1 more Smart Citation
“…The present method complements, therefore, the common approach of comparing multiple realizations of an ocean general circulation model, driven with different atmospheric forcings (e.g., Grégorio et al 2015;Sérazin et al 2015).…”
Section: Introductionmentioning
confidence: 99%